Production of 2, 5-dimethylfuran from 5-hydroxymethylfurfural over reduced graphene oxides supported Pt catalyst under mild conditions. (1st January 2016) - Shi, Juanjuan; Wang, Yingyu; Yu, Xini; Du, Weichen; Hou, Zhaoyin
Graphical abstract: Highlights: Pt/rGO is active and selective for the production of DMF from HMF under mild conditions. The yield of DMF reached 73.2% with a 100% conversion of HMF at 120 °C, 3.0 MPa H2 . The preferential adsorption of HMF on Pt/rGO would accelerate its conversion. Abstract: Reduced graphene oxides supported platinum (Pt/rGO) is extremely active and selective for the production of 2, 5-dimethylfuran (DMF) via hydrogenation of 5-hydroxymethylfurfural (HMF) among a series of supported Pt catalysts under mild conditions. The influence of varied reaction parameters, such as solvent, reaction temperature, H2 pressure, and HMF concentration were investigated with respect to the conversion of HMF and the yield of DMF. It was found that the yield of DMF reached 73.2% with a 100% conversion of HMF at 120 °C, 3.0 MPa H2 and 2.0 h.